Multidimensional autoconcept and healthy lifestyles in stomatology students - Universidad Privada de Huancayo Franklin Roosevelt - 2015 - Almonacid Sosa, Edgar Fernando (2020)
Objectives: To know the relationship between helathy lifestyles and multidimensional self-concept in stomatology students of the  Universidad Privada de Huancayo Franklin Roosevelt - 2015. Conclusion: It has been determined is a significant, high posititive correlation between healthy  lifestyles  and the dimensional self-concept of job satisfaction in stomatology students in the - Universidad Privada de Huancayo Franklin Roosevelt - 2015.